AVALIAÃ‡ÃƒO DA TOXICIDADE DE ALGUNS INSETICIDAS SOBRE O ð˜”ð˜¦ð˜µð˜¢ð˜³ð˜©ð˜ªð˜»ð˜ªð˜¶ð˜® ð˜¢ð˜¯ð˜ªð˜´ð˜°ð˜±ð˜ð˜ªð˜¢ð˜¦ (Metch.) Sorokin - Alves, SÃ©rgio Batista; Carvalho, Sueli Martinez de; Carvalho, Alfredo O. R. de (REVISTA DE AGRICULTURA, 2020)
AVALIAÃ‡ÃƒO DA TOXICIDADE DE ALGUNS INSETICIDAS SOBRE O ð˜”ð˜¦ð˜µð˜¢ð˜³ð˜©ð˜ªð˜»ð˜ªð˜¶ð˜® ð˜¢ð˜¯ð˜ªð˜´ð˜°ð˜±ð˜ð˜ªð˜¢ð˜¦ (Metch.) Sorokin